Yes, and how improvisation reverses "no, but" thinking and improves creativity and collaboration - Leonard, Kelly (New York HarperBusiness, 2015)
Executives from The Second City?the world?s premier comedy theater and school of improvisation?reveal improvisational techniques that can help any organization develop innovators, encourage adaptable leaders, and build transformational businesses.
Includes index.
Keywords: Second City (Theater company)